Pendampingan Orang Tua dalam Membangun Lingkungan Belajar yang Kondusif - Mardianti, Desi (PT Ruang Publikasi, 2025)
The important role of parental attention in motivating children to learn, by highlighting its significant impact on children's academic, psychological, and social development. Through consistent and in-depth attention, parents can not only help children overcome learning challenges, but also create an environment that supports the growth of children's confidence and motivation. The study identified two main types of motivation that are influenced by parental attention: intrinsic motivation, which is driven by the child's internal curiosity and satisfaction, and extrinsic motivation, which is influenced by external appreciation and recognition. In addition, emotional support from parents is essential for boosting children's self-confidence as well as helping them manage anxiety about failure, which often hinders their learning efforts. Consistency of parental attention also plays an important role in creating a stable and safe environment, which allows children to focus on their learning. The active involvement of parents in setting academic goals further strengthens the focus and motivation of children. Psychological theories such as Bandura's Social Learning Theory, Basic Needs Theory by Deci and Ryan, and Gardner's Multiple Intelligence Theory provide a deeper understanding of how parental attention affects not only academic performance, but also a child's emotional and psychological development. The results of this activity concluded that parental attention given lovingly and consistently is very important to motivate children to learn and support their overall development. The resulting recommendations include the need for training programs for parents in providing effective attention and the importance of collaboration between parents, schools, and communities in creating a supportive educational environment.